Building Academic Communities to Support Nursing Students with Disabilities: An Integrative Review - Leslie Neal-Boylan; Michelle Miller; Jessica Bell (The Ohio State University Libraries, 2018)
Background: Students with disabilities in higher education are increasing, yet discrimination against nurses and nursing students with disabilities persists.  A healthy academic community must include students with disabilities who are receiving accommodations per the ADAAA. Aim: To determine the extent, if any, of progress in accommodating nursing students with disabilities since the enactment of the Americans with Disabilities Act Amendment (ADAAA) of 2008. Methods: An integrative review of peer-reviewed literature written in English was conducted. The Cumulative Index to Nursing & Allied Health Literature (CINAHL), PubMed, and Educational Resources Information Center (ERIC) were searched. The date range spanned from 2008 to 2018. The type of peer-reviewed literature was not specified. Results: Accommodating students with disabilities depends on individual faculty who remain concerned about patient safety. Faculty tend to view students with disabilities using a medical rather than a social model and evaluate students on the ability to perform essential functions of the job instead of on student competencies. Conclusions: Faculty are more aware of the needs of nursing students with disabilities and the need to accommodate them, yet discrimination still occurs. Academic communities must not discriminate against students with disabilities and should structure an interdisciplinary approach that includes assistance from the university disability office, education of faculty about the ADAAA and the development of sustainable educational models that integrate the individualized needs of all learners.